The inner Struggles of Jack in William Golding’s Lord of The Flies: A Psychoanalytical Exploration - Rahman, Abdur; Jan, Iqra; Naeem, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2023)
This research looks at the psychoanalytical interpretation of Jack’s attempts to grab power in the light of Sigmund Freud’s psychoanalytical theory. Psychoanalysis of Jack gives a clear reflection of his mind’s unconscious working. Implicit id-dominated psychic patterns mainly construct his mind. Thus, the psychoanalytical lens of criticism lays a platform to delve deep into Jack’s unconscious makeup of mind as portrayed in the novel bringing out the understanding of his actions. The psychoanalytical study of Jack reveals the enormous impact of the id on Jack on Jack, who grows into becoming a symbol of lust for power, chaos, and savagery. This research focuses on the application of psychoanalytical theory to dive deep into the depth of Jack’s unconscious mind.